2022
DOI: 10.21037/jgo-21-818
|View full text |Cite
|
Sign up to set email alerts
|

Biliary cancer brain metastases: a multi-institution case series with case reports

Abstract: Background: Biliary cancers are rare, and few reported cases of brain metastases from primary biliary cancers exist, especially describing patients in the United States. This report assesses the proportion and incidence of brain metastases arising from primary biliary cancers [cholangiocarcinoma (CCA) and gallbladder cancer] at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Compared to lung, renal, and breast cancers, HPB brain metastases are rare [1,2]. The improved systemic management of these cancers has resulted in improved survival and recognition of the potential for late brain metastases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to lung, renal, and breast cancers, HPB brain metastases are rare [1,2]. The improved systemic management of these cancers has resulted in improved survival and recognition of the potential for late brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…Brain metastases from hepatocellular carcinoma (HCC), cholangiocarcinoma (CCC), and pancreatic carcinoma (PCC) are very rare, with incidence rates of 0.2-2.2%, 0.5-1.4%, and 0.3-0.6%, respectively [1][2][3]. The onset of brain metastases from these primary malignancies often represents a late manifestation of the primary disease.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Retrospective analyses by Falkson et al and Frega et al reported median OS times of approximately 7 and 3 months, respectively, highlighting the complexity of treatment decisions. [3,7] Supportive care remains the predominant treatment modality for brain metastasis, constituting 47% of the cohorts. [8] For patients tolerating therapies, local treatments such as neurosurgical resection, stereotactic radiosurgery (SRS), and whole-brain radiation therapy (WBRT) are considered as treatment options.…”
Section: Discussionmentioning
confidence: 99%